INTERCONNECTION BETWEEN RISK-TAKING AND PASSIONARITY OF PERSONS OF YOUNG AGE - Бикова, Світлана Валентинівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
This article examines the results of the theoretical and empirical study of the differences in the manifestations of predisposition to the risk of persons of young age with different degrees of passionarity. Risk-taking is seen as a psychological phenomenon, as a personality trait, characterized by the choice of risk-generating situations. It is possible to assume that the manifestations of predisposition to risk, is accompanied by passion, purposefulness, unselfish risk, sensory passions, activity, and perhaps even passionarity. For empirical testing, we chose the following psychodiagnostic methods “Test-questionnaire for quality indicators of predisposition to risk” (O. Sannikova, S. Bykova) and “Placing herself on the scale of passionarity” (modification of the methodology of T. Dembo and S. Rubinstein). An empirical study was conducted on the basis of Odessa State Academy of Civil Engineering and Architecture. The total number of subjects – 67 people, aged 19 to 23 years. The data obtained during the correlation analysis confirmed the validity of the comparison of qualitative characteristics of predisposition to risk and passionarity. Positive significant correlations were found between passionarity and such indicators of risk aversion as the ECR (Emotional Component) of risk appetite, ECR1 (active component of) risk susceptibility, and KAoR (Composite Risk Assessment) at 5%. Psychological characteristics of representatives with a high degree of passionarity and low were detected. Hence, high values indicate that such people are characterized by the independence of behavior and the freedom of expression of thought, the ability to lead, as well as the tendency to transform reality. Stable direction for the implementation of a functional sustainable goal in the subjective space, the desire for self-reflection, determination, spontaneity of the desire to express personality, responsibility for their actions, persistence, flexibility of behavior, a trusting attitude to the environment.